The role of pH and calcination process on CuFe2O4 nanoparticles synthesized by microwave-hydrothermal reactions - Thongtem T. (2014)
CuFe2O4 nanoparticles were synthesized by microwave-hydrothermal reactions in solutions of different pH values, and followed by the 450 °C calcination for 1 h. The products were then characterized using XRD, TEM and SAED, in order to determine the phase, particle sizes and orientations. It was found that the particle sizes, determined from Scherrer equation and TEM images, were increased with the increase in the basicity of the solutions. Thus the results have the influence on the product properties. ©2010 IEEE.